Akulturasi Nilai Budaya Islam Dalam Upacara Pelet Betteng di Madura - Astriana Putri; Rofi’us Syan Adityawarman; Wilhelmina Hariyadi; Millatuz Zakiyah (Islamic Insights Journal, 2023)
This study aims to describe the acculturation of Islamic cultural values ​​which include processions, the meaning of tools and materials, and the social values ​​of the Notonegoro perspective contained in the pèlèt betteng tradition in the people of Pademawu District, Pamekasan Regency, Madura. This research has an urgency as a written documentation of ancestral heritage that should be preserved and implemented. This research is a qualitative research type with a field research design. Research subjects were selected through a purposive sampling technique. The data collected in this study consisted of two data, namely the main data in the form of research subject interview data and other supporting data. The data analysis method used is inductive analysis. The results showed that the procession of the pèlèt betteng ceremony in Pademawu District, Pamekasan Regency had six core processions, namely ngajjhi, pèlèt betteng, neḍḍhâ nyèyor ban tellor, siraman, bhânteng nyèyor, and rojhâk gobet. The meaning contained in the tools and materials also uses more meaning that comes from the view of life of the community itself. In addition, there are three social values ​​from Notonegoro's perspective in the traditional ceremony of pèlèt betteng for the people of Pademawu District, Pamekasan Regency, namely material values, vital values, and spiritual values. Keywords: Pèlèt Betteng; Procession; Meaning; Notonegoro Social Values